INCREASING PROTEIN STABILITY BY IMPROVING BETA-TURNS - Fu, Hailong (2009)
Our goal was to gain a better understanding of how protein stability can be increased by improving β-turns. We studied 22 β-turns in nine proteins with 66 to 370 residues by replacing other residues with proline and glycine and measuring the stability. These two residues are statistically preferred in some β-turn positions. We studied: Cold shock protein B (CspB), Histidine-containing phosphocarrier protein (HPr), Ubiquitin, Ribonucleases Sa2, Sa3, T1, and HI, Tryptophan synthetase α-subunit (TSα), and Maltose binding protein (MBP). Of the fifteen single proline mutations, 11increased stability (Average = 0.8 ± 0.3; Range = 0.3 – 1.5 kcal/mol), and the stabilizing effect of double proline mutants was additive. Based on this and our previous work, we conclude that proteins can generally be stabilized by replacing non-proline residues with proline residues at the i + 1 position of Type I and II β-turns and at the i position in Type II β-turns. Other turn positions can sometimes be used if the φ angle is near −60° for the residue replaced. It is important that the side chain of the residue replaced is less than 50% buried. Identical substitutions in β-turns in related proteins give similar results. Proline substitutions increase stability mainly by decreasing the entropy of the denatured state. In contrast, the large, diverse group of proteins considered here had almost no residues in β-turns that could be replaced by Gly to increase protein stability. Improving β-turns by substituting Pro residues is a generally useful way of increasing protein stability.